1H, 13C, and 15N chemical shift assignments of ZCCHC9 - Sanudo, Maria; Jacko, Martin; Rammelt, Christiane; Vanacova, Stepanka; Stefl, Richard (Biomolecular NMR assignments, 2011)
ZCCHC9 is a human nuclear protein with sequence homology to yeast Air1p/Air2p proteins which are RNA-binding subunits of the Trf4/Air2/Mtr4 polyadenylation (TRAMP) complex involved in nuclear RNA quality control and degradation in yeast. The ZCCHC9 protein contains four retroviral-type zinc knuckle motifs. Here, we report the NMR spectral assignment of the zinc knuckle region of ZCCHC9. These data will allow performing NMR structural and RNA-binding studies of ZCCHC9 with the aim to investigate its role in the RNA quality control in human.
Keywords: RNA-Binding Proteins; Nuclear Proteins; proteiny vázající RNA; Carbon Isotopes; lidé; Hydrogen; Nuclear Magnetic Resonance, Biomolecular; izotopy uhlíku; vodík; nukleární magnetická rezonance biomolekulární; jaderné proteiny; Nitrogen Isotopes; izotopy dusíku; Humans